Older Adults Bereaved by Suicide: A Systematic Literature Search Identifying Zero Studies. Issue 1 (2nd January 2020) - Hybholt, Lisbeth; Buus, Niels; Erlangsen, Annette; Lauge Berring, Lene
Abstract : The objective of the present study was to identify empirical studies of older adults (≥60) bereaved by the loss of a significant other to suicide. A systematic literature search in CINAHL, Embase, Medline, PsycINFO, and SCOPUS was conducted. The inclusion criteria were empirical studies investigating people bereaved by suicide at age ≥60 published in English or a Nordic language. Although a total of 12, 871 references were identified, after screening, no articles fulfilled the inclusion criteria. The study led to the conclusion that there is a lack of research on older adults bereaved by suicide. With the aim of tailoring evidence-based interventions to this group, future research should investigate whether they have particular experiences, psychosocial responses and needs, and help-seeking strategies.